The Route Choice Analysis of Parung-Sentul Traveler: A Case of Impact New Toll Road Operation - Said Suganda; Andri Irfan Rifai; Joewono Prasetijo (International Journal Labs, 2022)
The selection of a good travel route can be efficient distance, travel time, and travel costs required. The purpose of this study was to determine the characteristics of travelers from the Parung community in driving to Sentul and modeling the selection of travel routes based on the characteristics that express the probability of individuals choosing the route and analyze the preferences of the selection of routes from the Parung community to the Bogor Ring Road Section IIIA toll road (Simpang Yasmin – Kayu Manis Segment). This study uses a questionnaire method (google form) which is used as a tool to collect data from respondents following predetermined criteria following existing factors based on the theory of stated preference. The Data obtained were tested first validity and reliability using SPSS software. The results showed that the toll road is the primary choice of most respondents, with a percentage of 72% higher than the arterial road based on the effectiveness of travel time, route comfort, fuel effectiveness, facilities, travel time, and barriers.